Sistema de gestão da qualidade: estudo em obra do Programa Minha Casa Minha Vida no interior de São Paulo - Nascimento, Odirlei Garcia do (2017)
The present work presents a study carried out with a company in the field of civil construction, with the objective of performing an analysis of the requirements of the Brazilian program of quality and productivity in the work habitat linked to the program my home my life of the federal government and ISO 9001. The methodology of this study was initially to carry out research on the subject and other related where it provided as a basis for the elaboration of visits and data collection in relation to the application of the requirements of each management system, including internal audits, external audits and periodic inspections. A construction company was selected in the interior of the state of São Paulo, which participates in the program my house my life as a way of collecting the data to complete the results. Based on this information, it was possible to analyze improvements to the process and to better manage the requirements. Among the results found was that there is no difference between medium and small organizations, the maintenance of the management system is effective when the planning is accomplished, standardization is possible to be obtained when having a corporate management, having employees with functions exclusive to the management system is quite fundamental, among others.